Blebbistatin and blebbistatin-inactivated myosin II inhibit myosin II-independent processes in Dictyostelium - Shu, Shi (National Academy of Sciences, 2005)
Blebbistatin, a cell-permeable inhibitor of class-II myosins, was developed to provide a tool for studying the biologic roles of myosin II. Consistent with this use, we find that blebbistatin inhibits three myosin II-dependent processes in Dictyostelium (growth in suspension culture, capping of Con A receptors, and development to fruiting bodies) and does not inhibit growth on plates, which does not require myosin II. As expected, macropinocytosis (myosin I-dependent), contractile vacuole activity (myosin V-dependent), and phagocytosis (myosin VII-dependent), none of which requires myosin II, are not inhibited by blebbistatin in myosin II-null cells, but, unexpectedly, blebbistatin does inhibit macropinocytosis and phagocytosis by cells expressing myosin II. Expression of catalytically inactive myosin II in myosin II-null cells also inhibits macropinocytosis and phagocytosis. Both blebbistatin-inhibited myosin II and catalytically inactive myosin II form cytoplasmic aggregates, which may be why they inhibit myosin II-independent processes, but neither affects the distribution of actin filaments in vegetative cells or actin and myosin distribution in dividing or polarized cells. Blebbistatin also inhibits cell streaming and plaque expansion in myosin II-null cells. Our results are consistent with myosin II being the only Dictyostelium myosin that is inhibited by blebbistatin but also show that blebbistatin-inactivated myosin II inhibits some myosin II-independent processes and that blebbistatin inhibits other activities in the absence of myosin II.